2014
DOI: 10.3109/03630269.2014.880715
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Overload in Very Young Children with Limited Thalassemia Care Resources in South China

Abstract: Southern China has one of the world's largest population of patients needing transfusions. Transfusion and chelation are not uniformly available and no magnetic resonance imaging (MRI) assessment data exists to date. A total of 153 young β-thalassemia major (β-TM) patients were assessed using a validated 1.5T scanner in Hong Kong, People's Republic of China (PRC). Their median age was 13 (range 7 to 30), and most patients were young (22.0% age <10, 73.0% age <15, 88.0% age <18). Erratic health care made estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…While in the studies that reported significant correlations between liver and heart iron, the number and proportion of severe LIO patients were high . In the study by Au et al, severe liver iron loading was found in the majority of patients (accounting for 55.0%; n = 153). In our study, 64 patients had severe LIO, accounting for 58.18%, which is similar to that of Au et al Meanwhile, from the curve fit acquired, poor correlation between liver and heart iron in the normal or mild LIO segments can be clearly seen, whereas they had a close relationship in the severe LIO segment.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…While in the studies that reported significant correlations between liver and heart iron, the number and proportion of severe LIO patients were high . In the study by Au et al, severe liver iron loading was found in the majority of patients (accounting for 55.0%; n = 153). In our study, 64 patients had severe LIO, accounting for 58.18%, which is similar to that of Au et al Meanwhile, from the curve fit acquired, poor correlation between liver and heart iron in the normal or mild LIO segments can be clearly seen, whereas they had a close relationship in the severe LIO segment.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies reported that liver iron levels had no significant linear correlations with heart iron . But other studies reported that significant correlations existed between them . One possible explanation that can reconcile this disparity is that a delay exists in the loading and unloading of heart iron with respect to liver iron .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics analyses by t test showed significant differences in serum ferritin levels between the MBT and control groups (p value = 0.0004). A study in China also found high serum ferritin levels in MBT patients, 2754 µg/L [16]. Another study on Egyptian children with MBT also found high serum ferritin levels, 4510 µg/L [17].…”
Section: Statistical Analysesmentioning
confidence: 89%
“…Currently, it is particularly difficult to identify compatible donors in China due to the nation's one‐child policy. Moreover, many patients with TM cannot financially afford long‐term supportive care with normative blood transfusions and iron chelation . Thus, although thalassaemia‐free survival (TFS) rates have increased to 52–82% following HSCT, an alternative source of donors is urgently needed.…”
Section: Introductionmentioning
confidence: 99%